DEPARTMENT OF HYPERTENSION AND CARDIORENAL MEDICINE, DOKKYO MEDICAL UNIVERSITY, TOCHIGI - Shigeo Horinaka; Akihisa Yabe; Hiroshi Yagi; Toshihiko Ishimitsu; Tsutomu Yamazaki; Shinya Suzuki; Takahide Kohro; Ryozo Nagai (Российский кардиологический журнал, 2011)
Nicorandil has cardioprotective effects in the ischemic myocardium, mimicking ischemic preconditioning, and is thus expected to improve the prognosis of ischemic heart disease (IHD). As part of the Japanese Coronary Artery Disease (JCAD) Study, a multi-centre collaborative prospective observational study of a large cohort of coronary artery disease patients, the effect of nicorandil on outcome was examined. In total, 2,558 patients with nicorandil treatment and controls subjected to propensity score matching were eligible among 13,812 patients registered in the JCAD study. The mean follow-up interval was 2,7 years. The primary endpoint, death from all causes, was significantly lower, by 35% (hazard ratio 0,65, p=0,0008), in the nicorandil group than in the control group. There were also significant reductions in secondary endpoints, including cardiac death (56%), fatal myocardial infarction (56%), cerebral or vascular death (71%), and congestive heart failure (33%) in the nicorandil group, with no excess of deaths from other non-cardiovascular causes. Treatment with nicorandil reduced the number of deaths from all causes to a similar extent with or without treatment with sulfonylureas. The reduction in cardiovascular death with nicorandil was large in patients with IHD, which has important implications for treatment.